Cognitive outcomes in patients treated with neuromuscular electrical stimulation after coronary artery bypass grafting - Lo Re, Vincenzina; Russelli, Giovanna; Lo Gerfo, Emanuele; Alduino, Rossella; Bulati, Matteo; Iannolo, Gioacchin; Terzo, Danilo; Martucci, Gennaro; Anzani, Stefano; Panarello, Giovanna; Sparacia, Gianvincenzo; Parla, Giuseppe; et al. (Frontiers in Neurology, 2023)
Objective Mechanisms of neurocognitive injury as post-operative sequelae of coronary artery bypass grafting (CABG) are not understood. The systemic inflammatory response to surgical stress causes skeletal muscle impairment, and this is also worsened by immobility. Since evidence supports a link between muscle vitality and neuroprotection, there is a need to understand the mechanisms by which promotion of muscle activity counteracts the deleterious effects of surgery on long-term cognition. Methods We performed a clinical trial to test the hypothesis that adding neuromuscular electrical stimulation (NMES) to standard rehabilitation care in post-CABG patients promotes the maintenance of skeletal muscle strength and the expression of circulating neuroprotective myokines. Results We did not find higher serum levels of neuroprotective myokines, except for interleukin-6, nor better long-term cognitive performance in our intervention group. However, a greater increase in functional connectivity at brain magnetic resonance was seen between seed regions within the default mode, frontoparietal, salience, and sensorimotor networks in the NMES group. Regardless of the treatment protocol, patients with a Klotho increase 3 months after hospital discharge compared to baseline Klotho values showed better scores in delayed memory tests. Significance We confirm the potential neuroprotective effect of Klotho in a clinical setting and for the first time post-CABG.